The university and its role in developing political awareness among youth: A field study at the University of Sulaimani - Salih, Miran; Husein, Twana (Al-Adab Journal, 2023)
This study focuses on the role of the university in developing political awareness among youth. The main questions of the research are whether the university has a positive role in promoting a sense of patriotism among young people? Does the university have a role in educating students about the challenges faced by the community Therefore, the problem of the research lies in trying to answer the above questions through the implementation of field procedures. But with regard to the objectives of the research, it seems that the researchers have two goals and try to discuss them through the field steps of the research. The first objective is to measure the role of the university in raising political awareness among young people from the perspective of university students. The second objective is to distinguish between students’ perceptions of the university’s role in educating political youth according to each of its variables: gender, college, academic level, and political affiliation. This study is a descriptive study in which the social survey method was used in a sampling manner for this purpose. An intentional sample of (100) male and female students from the University of Sulaimani was selected from each of the faculties of sciences and human sciences. Thus, 50 male and female students were accepted in the Department of Sociology for the third and fourth stages. The College of Humanities and (50) male and female students in the Physics Department of the Faculty of Science of both sexes. With regard to the research tools, the researchers used the Likert quintuple scale to build the scale, and then an attempt was made using the SPSS program to conduct the necessary analysis of the scale’s paragraphs and discuss the research objectives in a scientific manner based on descriptive statistics. The results also showed that there were statistically significant differences between students in the educational stage, but no There are statistically significant differences between students in other variables.